FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELOLAAN KEUANGAN KELUARGA DI DESA UNTANG KALIMANTAN BARAT - Shanti, Shanti Veronica br Siahaan; Tjondro Sugianto , Helena Anggraeni (PRPM (Pusat Riset dan Pengabdian Pada Masyarakat) Institut Shanti Bhuana, 2020)
Research on the factors that influence family financial management in Untang village, Banyuke Hulu sub-district, Landak Regency, West Kalimantan using qualitative phenomenological research methods. The research data was taken using semi-structured interview techniques and observations. This study involved three housewives’ participants who had been married for more than ten years, have more than two children and lived in the village. The results of this study found that the factors that influence financial management are the appreciation of the Dayak traditions, openness to the advancement of children's education and the limited ability to manage business capital owned today.